Effects of Aspergillus spp. Phospholipase to Induce Histological and Biochemical Changes in Male Rats - T. Jasim, Saif; Hamad Saleh, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
This study was achieved to exhibit the effects of Aspergillus spp. phospholipase on rats (in vivo). In this study, 18 adult albino male rats were used, which were divided into three groups including the control group (received ad libitum), the second group (injected with 0.05 ml/animal of phospholipase), and the third group (injected with 0.1 ml/animal of phospholipase) for 3 weeks. The results showed a highly significant increase (p<0.05) in levels of IL-1α, IL-2, IL-6, and IL-8 in the second and third groups compared with the control group. Oxidative stress factors in the second and third groups exhibited a significant increase (p<0.05) in levels of MDA (malondialdehyde) and glutathione (GSH) compared with the control group. About the histological changes, the liver sections that were prepared from the second and third groups showed the degeneration of hepatocytes, thickening of the wall of central veins with inflammatory cell infiltration, and different changes in nuclei in many hepatocytes. It was concluded that phospholipase that was extracted from Aspergillus spp. led to remarkable histological and biochemical changes in rats.